2021
DOI: 10.3390/ijms221910841
|View full text |Cite
|
Sign up to set email alerts
|

Skin Barrier Dysregulation in Psoriasis

Abstract: The skin barrier is broadly composed of two elements—a physical barrier mostly localised in the epidermis, and an immune barrier localised in both the dermis and epidermis. These two systems interact cooperatively to maintain skin homeostasis and overall human health. However, if dysregulated, several skin diseases may arise. Psoriasis is one of the most prevalent skin diseases associated with disrupted barrier function. It is characterised by the formation of psoriatic lesions, the aberrant differentiation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 268 publications
1
56
0
1
Order By: Relevance
“…PTPμ interacts with vascular endothelial (VE)-cadherin and regulates both the tyrosine phosphorylation state of VE-cadherin and the integrity of the barrier function [ 60 ]. In a similar perspective, these results can be extrapolated to psoriatic skin, which is also characterized by an impaired epidermal barrier function [ 61 , 62 , 63 ]. PTPμ is also known to interact with other classical cadherins, including epithelial (E-) cadherin [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…PTPμ interacts with vascular endothelial (VE)-cadherin and regulates both the tyrosine phosphorylation state of VE-cadherin and the integrity of the barrier function [ 60 ]. In a similar perspective, these results can be extrapolated to psoriatic skin, which is also characterized by an impaired epidermal barrier function [ 61 , 62 , 63 ]. PTPμ is also known to interact with other classical cadherins, including epithelial (E-) cadherin [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the histological analysis of recovering human and mouse wounds indicated that OLFM4 was induced at the proliferative phase of wound healing, we next sought to investigate whether its expression pattern was altered in skin disorders. Psoriasis is a chronic inflammatory skin disorder characterized by keratinocyte hyperproliferation [ 25 ] and is accompanied by accelerated wound healing [ 26 ]. Examination of OLFM4 expression in psoriatic lesional skin showed increased levels of the protein in epidermis compared to healthy skin (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hyperproliferation with altered-differentiation of keratinocytes are the main characteristics of psoriasis [ 37 ]. The disrupted skin barrier promotes subsequent immune dysfunction, which contributes to the maintenance of inflammatory skin microenvironment of psoriasis [ 38 ]. To determine whether AEC-SC or UMSC-SC affect the integrity of skin barrier, we investigated the proliferation and differentiation of keratinocytes.…”
Section: Resultsmentioning
confidence: 99%